2020
DOI: 10.1111/ele.13495
|View full text |Cite
|
Sign up to set email alerts
|

The worldwide impact of urbanisation on avian functional diversity

Abstract: Urbanisation is driving rapid declines in species richness and abundance worldwide, but the general implications for ecosystem function and services remain poorly understood. Here, we integrate global data on bird communities with comprehensive information on traits associated with ecological processes to show that assemblages in highly urbanised environments have substantially different functional composition and 20% less functional diversity on average than surrounding natural habitats. These changes occur w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
118
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 69 publications
(119 reference statements)
11
118
2
Order By: Relevance
“…The results from this study, although restricted to South Australia, can be interpreted on a broader context. Avian ecosystems have undergone profound change due to the increasing threat of urbanisation, which creates disparity in the richness and diversity of the environment [ 22 , 23 , 24 ]. Urbanisation challenges avian species by creating threats to their survival through decreased food availability and increased air, light and noise pollution, which results in compromised immune function due to stress [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study, although restricted to South Australia, can be interpreted on a broader context. Avian ecosystems have undergone profound change due to the increasing threat of urbanisation, which creates disparity in the richness and diversity of the environment [ 22 , 23 , 24 ]. Urbanisation challenges avian species by creating threats to their survival through decreased food availability and increased air, light and noise pollution, which results in compromised immune function due to stress [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This pattern can be explained by (1) the loss of the most specialized species strictly associated with natural habitats (which leads to a decrease in C-values), and (2) the predominance, in the suburban and urban areas, of synanthropic and generalist species (Faeth et al 2011), which results in higher faunal homogenization (McKinney 2006), and hence lower species accumulation rates (z-values). Sol et al (2020), in a global study on bird functional diversity along urbanization gradients, found that the loss of functional diversity in moderately and highly urbanized environments relative to surrounding natural and rural habitats reflects a decrease in both species richness and abundance evenness. It is possible that a reduction in functional diversity, due to the loss of functionally redundant species, is also implied in the reduced species richness observed in the urban sectors of our study area.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of such traits—functional diversity—captures variation in the ecological roles of species (Tilman 2001 ; Violle et al 2007 ; Díaz et al 2020 ). Although ecologists have traditionally focused on taxonomy-based metrics of biodiversity, incorporating functional diversity allows a more complete view of how communities respond to environmental gradients and human pressures (Mouillot et al 2013 ; Teixidó et al 2018 ; Sol et al 2020 ; Muguerza et al 2020 ), elucidates the relationships between biodiversity and ecosystem functioning (e.g. Griffin et al 2009 ; Lefcheck and Duffy 2015 ), and reveals the operation of niche-based processes during community assembly (Mcgill et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%